Keanekaragaman Spesies Nyamuk di Daerah Transmission Assesment Survey (TAS) Filariasis di Kabupaten Enrekang, Provinsi Sulawesi Selatan - Malonda Maksud; Sitti Chadijah; Hasrida Mustafa; Ade Kurniawan; Murni Murni (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2020)
Enrekang Regency was declared to have passed third Transmission Assesment Survey (TAS), since there were no positive Brugia Malayi in elementary school students. The aspect of filariasis vector must be considered in this disease transmission. This study aims to determine the diversity of mosquitoes and their potential as vectors of filariasis in the TAS area in Enrekang Regency, South Sulawesi Province. This research is part of a multicenter study in 2017. This study was conducted with a cross-sectional study. Mosquitoes were collected in Parombean Village and Potokulin Village by modifying the Human Landing Catches (HLC) method with the human-baited double net trap from 18:00 to 06:00. The results showed that 30 species found in Parombean Village, consisted eight genera and Culex vishnui was the most abundant species. In Potokulin Village, 11 species were found consisted in five genera and Cx. quinquefasciatus was the most abundant species. The average age of mosquitoes was around 8-24 days. The species of mosquito as vector potential of filariasis in this area is Cx. vishnui, Cx, quinquefasciatus, and Anopheles barbirostris.